Solid-liquid phase behavior of eutectic solvents containing sugar alcohols - Silva, Liliana P. (2018)
Mixtures of carbohydrates are often reported in the literature as deep eutectic solvents yet, in most cases, their solid–liquid phase diagrams are poorly characterized and no evidence is available to validate this classification. In this work, the phase diagrams of the binary systems composed of the sugar alcohols mannitol or maltitol and meso-erythritol, xylitol, or sorbitol, were experimentally determined. The results obtained reveal that these systems have a thermodynamic ideal behavior, questioning their classification as deep eutectic solvents and showing that intermolecular hydrogen bonding between the components of a mixture is not a sufficient condition to prepare deep eutectic solvents. The phase diagrams of the systems composed of mannitol or maltitol and cholinium chloride were also measured in this work. In sharp contrast to the mixtures composed solely by sugar alcohols, and unlike numerous other choline-based eutectic systems reported in the literature, these systems revealed significant deviations to thermodynamic ideality, leading to significant melting temperature depressions. The Cl-OH interaction between cholinium chloride and the sugar alcohols is identified as the main reason for these deviations to ideality, paving the way for the rational choice of hydrogen bond acceptors to prepare deep eutectic solvents.